2017
DOI: 10.1111/cga.12255
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an international volunteer surgical project for patients with cleft lip and/or cleft palate: A mission in developing Laos

Abstract: Cleft lip and/or palate (CL/P) is a common birth defect of complex etiology. CL/P surgery is generally performed in infancy to allow for improvements in esthetics, suckling, and speech disorders as quickly as possible. We have engaged in activities such as free-of-charge surgery for CL/P a total of 12 times from 2001 to 2016 in Lao People's Democratic Republic (Laos). The United Nations has designated Laos as a Least Developed Country; it is one of the poorest countries in Asia. We have carried out our activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…CLP cases were ranked first when it comes to the number of patients, namely as many as 163 cases, followed by CL with as many as 57 cases, and the last one, CP with 16 cases. This is similar to the results of a study conducted by Goto et al, [16] in 2018 in Laos, which had the occurrence of CLP ranked first, followed by CL and finally by CP. Another research conducted by Yaqoob et al, [17] in 2013 in Pakistan, found the incidence of CP higher than that of CLP and CL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CLP cases were ranked first when it comes to the number of patients, namely as many as 163 cases, followed by CL with as many as 57 cases, and the last one, CP with 16 cases. This is similar to the results of a study conducted by Goto et al, [16] in 2018 in Laos, which had the occurrence of CLP ranked first, followed by CL and finally by CP. Another research conducted by Yaqoob et al, [17] in 2013 in Pakistan, found the incidence of CP higher than that of CLP and CL.…”
Section: Discussionsupporting
confidence: 91%
“…[20] Variations in CL/P at Yayasan Surabaya CLP Center were then divided based on gender, and the result for CLP type was 91 male patients and 72 female patients, that for CL type was 36 male patients and 21 female patients, and that for CP type was 13 female patients and 3 male patients. In the case of CLP and CL, the frequencies of patients were higher for males although not significant, whereas for CP, the frequency of patients was strongly associated with females, this is in line with the conclusion expressed in many studies such as the ones by Martelli et al [20] (2012), Agbenorku [5] (2013), and especially the one by Goto et al, [16] in Laos, which has the same ethnicity as Indonesia, that is, Asians, stating that CLP and CL occur mostly in male. [19] On the contrary, CP was more prevalent in females than that in males, this result was in accordance with the research conducted by Nagase et al [19] (2011) in Japan, which also had the same ethnicity as Indonesia and which was conducted on 184 patients with CL/P and showed a higher percentage of females experiencing CP than males.…”
Section: Discussionsupporting
confidence: 87%
“…Fortunately, humanitarian surgical missions for patients with CLP in developing countries have a long history. Non-governmental, mission-based organizations such as Smile Train, Operation Smile, and Interplast2 as well as smaller scale, charitable groups345 have conducted global missions for CLP care in low-income countries. The World Health Organization recognized more than 55 countries as in danger of “health workforce crisis” and in need of education and development of a novel CLP training program6.…”
mentioning
confidence: 99%
“…The prevalence of orofacial clefts and patients' satisfaction with their treatment outcome has been analyzed sufficiently in developed countries, but in developing countries there is still a lack of data examining clefts. [16][17][18][19] There are studies examining the prevalence of clefts and postoperative complications in small patient groups in developing countries during humanitarian missions, [20] but there is no data regarding patients' levels of satisfaction with their surgical outcome. Because of the country's infrastructure the collection of data on surgical outcome and even short period follow-up can be very difficult.…”
Section: Discussionmentioning
confidence: 99%